O gigante acordou: uma análise discursiva dos protestos de junho de 2013 em três gestos - Lopes, Tiago Alves da Silva (2021)
The June 2013 protests are opaque and are still disputed today. In view of a new look at this remarkable event, we have worked, throughout this dissertation, with a vertical analysis of the statement “the giant woke up” in three analytical gestures based on the theory of Materialist Discourse Analysis. The statement does not appear on the first day of the demonstrations, but begins to circulate when the demonstrations are in the second stage, spread over several cities. The “giant wakes up” when the agenda for the revocation of the increase in transportation tickets, the twenty cents, is swallowed up by the mass demonstrations in the next stage of the protests. In the first gesture, we suggest the utterance-object category as a corpus that unfolds in different materialities, starting from the same linearity, initially meaning the large volume of bodies on the streets in an effect of self-identification with the protesting mass. Next, we consider the opacity of the protests, analyzing their historicity in the midst of capitalism, law and the consecration of the Nation-State, and, based on this analysis, we propose the form/body-protest category, ending up by verifying the crossings of anti-communism in the statement. Finally, we analyze the effects of neoliberalism on protests, through the statement, highlighting the symbolic points that the June Journeys inaugurate. We seek, throughout the work, to provide new perspectives, based on later events and on contributions already given to our object.